A Novel Method to Improve Data Deduplication System - Walse, K. H (International Journal of Computer Sciences and Engineering, 2025)
In large organizations same data is stored on the different places by different users. This will occupy the storage space. In the duplicate removal process one can remove the file duplicate with the original file and make space empty for the further storage. It works by eliminating redundant data and ensuring that only one unique instance of the data is actually retained on storage. The data deduplication technique works by tracking each data file and eliminate each file that it found more than one copy of it in the storage. There are many techniques for deduplication. Our proposed algorithm depends on reducing the data before it's stored in the storage or backup. Basically the procedure is the system analyses the data before storing it by one of mechanism for checking like hash value. If the system found the same data is stored already, ignore the data or document else store the data and save its analysis for future processing. There are many advantages by using this technique. No need for extra storage space